No Country for Old X-Men: The Aging Hero in No Country for Old Men and Logan - Ljubica Matek; Zvonimir Prtenjača ([sic], 2020)
The American Western is imbued with a particular elasticity, which allowed it to stay relevant for decades. One of the recent developments in the genre seems to be its focus on the aging frontiersman – a hero past its prime. A faithful adaptation of Cormac McCarthy’s 2005 novel, the Coen brothers’ eponymous film No Country for Old Men (2007), departs from the traditional Western by outlining an aging lawman, Sheriff Ed Tom Bell, struggling to live up to his role. Similarly, James Mangold’s Logan (2017) forces the titular pop-cultural superhero icon to endure the deconstruction of its archetypal alter ego, the Wolverine. The underlying themes of the two films intersect, representing their aging protagonists both as evocations of their own previous, abler selves, and as elderly frontiersmen in a world with hardly any space for aged (super)heroes. Their fluctuating identities challenge the traditional, idealistic representations of patriarchal Western heroes by introducing a more realistic and complex concept of an aging hero both into the universe of the neo-Western genre and into popular culture.